Pelatihan Pembuatan Website Menggunakan Wordpress Pada SMK Pangeran Antasari - Wahyuni, Linda; Rosnelly, Rika; Hardianto, Hardianto; Sari, Rita Novita; Rahayu, Sri Lestari; Khairi, Ibni (Publikasi Pengabdian Masyarakat, 2025)
The rapid advancement of digital technology highlights the importance of mastering website development skills, especially for vocational high school students who are being prepared for the workforce. This training aimed to improve the understanding and skills of students at SMK Pangeran Antasari in creating and managing websites using the WordPress platform, known for its user-friendly interface and minimal programming requirements. The activity involved 30 students from grades XI and XII in the Computer and Network Engineering program, divided into two groups to ensure effective learning. The training was carried out in five sessions: an introduction to WordPress and the importance of website development in the digital era; WordPress installation; content creation using the Gutenberg editor; theme and plugin management; and an independent implementation session where students designed their own websites. The training adopted a hands-on approach, with direct assistance provided to ensure thorough understanding of each technical stage. The results indicated a significant improvement in students' ability to independently create websites. They were able to manage website layouts, add multimedia content, and integrate additional features such as contact forms and galleries. Beyond technical skills, the training also fostered students’ creativity in designing websites for portfolios, blogs, or entrepreneurial purposes. In conclusion, WordPress-based training effectively strengthened the digital competencies of vocational high school students, particularly in creating informative and functional websites. This initiative is expected to provide valuable preparation for the technology-driven job market and can serve as a model for similar training programs in other schools. Keywords: Wordpress, Training, Website Development, Vocational Students, Digital Skills